Investigation of Electromagnetic Wave Propagation in Triple Walled Carbon Nanotubes - Basmaci, Ayşe Nihan; Filiz, Seckin (International Journal of Computational and Experimental Science and Engineering, 2024)
This study examines the behavior of electromagnetic wave propagation in a unique and complex three-walled carbon nanotube structure. The structure is formed by nesting three distinct nanotubes, and the interactions between them are thoroughly analyzed, taking into account their varying electromagnetic, material, and nano properties. The structure is designed at a nanoscale to provide a comprehensive description of electromagnetic wave propagation, including the electromagnetic interaction between the second nanotube, located in the middle of the structure, and the other two nanotubes situated in both the inner and outer portions of the structure. This study presents novel findings that differ from existing literature on the subject, contributing to our understanding of this important area of research.